2000
DOI: 10.1083/jcb.151.2.467
|View full text |Cite
|
Sign up to set email alerts
|

The Triad Targeting Signal of the Skeletal Muscle Calcium Channel Is Localized in the Cooh Terminus of the α1S Subunit

Abstract: The specific localization of L-type Ca2+ channels in skeletal muscle triads is critical for their normal function in excitation–contraction (EC) coupling. Reconstitution of dysgenic myotubes with the skeletal muscle Ca2+ channel α1S subunit restores Ca2+ currents, EC coupling, and the normal localization of α1S in the triads. In contrast, expression of the neuronal α1A subunit gives rise to robust Ca2+ currents but not to triad localization. To identify regions in the primary structure of α1S involved in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 47 publications
(77 reference statements)
5
95
3
Order By: Relevance
“…A second role that has been described for the C terminus is in targeting. In particular, C-terminal residues 1607-1661 (42) have been reported to be important for the targeting of ␣ 1S to the junctional membrane, and the mutation V1642D in this region was reported to impair targeting (43). However, we found that targeting of ␣ 1S could still occur when a fluorescent protein was attached to the C terminus truncated at 1636.…”
Section: Discussioncontrasting
confidence: 48%
“…A second role that has been described for the C terminus is in targeting. In particular, C-terminal residues 1607-1661 (42) have been reported to be important for the targeting of ␣ 1S to the junctional membrane, and the mutation V1642D in this region was reported to impair targeting (43). However, we found that targeting of ␣ 1S could still occur when a fluorescent protein was attached to the C terminus truncated at 1636.…”
Section: Discussioncontrasting
confidence: 48%
“…Previously we demonstrated that, in the absence of ␣ 1 subunits, ␣ 2 ␦-1 is misstargeted (14,18). Thus, for proper targeting, the ␣ 2 ␦-1 subunit needs to associate with an ␣ 1 subunit, which contains a C-terminal triad-targeting signal (19), but ␣ 2 ␦-1 itself does not contribute to triad targeting of the Ca 2ϩ channel complex.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, portions of the C terminus of α 1C (Gao et al, 2000) and α 1S (Proenza et al, 2000) may be important both for traffi cking to the plasma membrane, and for targeting to plasma membrane junctions with the SR (Flucher et al, 2000b;Proenza et al, 2000). Moreover, biochemical studies have suggested that the C-terminal residues 1393-1527 of α 1S bind calmodulin and can bind to RyR1 (Sencer et al, 2001).…”
Section: Streptavidin Accessibilitymentioning
confidence: 99%